Curing and Thermal Behaviour of N,N’-Diglycidyl benzophenone Tetracarboxydiimide Resin Using Mixture of Nadic/or Maleic Anhydride and 4,4’-Diaminodiphenylsulphone - Kumar, Vinay; Kumar, Lalit; Deep, Gagan (Asian Journal of Chemistry, 2011)
Curing studies of N,N'-diglycidyl benzophenone tetracarboxydiimide epoxy resin in the presence of maleic anhydride/or nadic anhydride or mixture of maleic anhydride/nadic anhydride: 4,4'- diaminodiphenyl sulfone in varying molar ratios were investigated using differential scanning calorimetry. Thermal stability of the isothermally cured resins was evaluated by thermogravimetry.